Psychological injuries in young boxers - Yang, F.; Yi, X.; Liu, J. (Revista Brasileira de Medicina do Esporte, 2023)
Introduction: Boxing is a fighting sport, and many factors cause physical injuries in athletes because of how they compete and train. Injuries are common for athletes who usually participate in this sport. Based on this, the relationship between positive psychological quality at the sport level should be explored, providing a theoretical basis for cultivating optimistic personalities in young athletes. Objective: Analyze the psychological injuries in young boxers to establish a standard to improve the psychological quality evaluation system of young athletes in China. Methods: By comparing the characteristics of different injuries, the possibility of injury occurrence in different activities can be explored, providing a theoretical basis to guide injury prevention, then promoting sports injury prevention. Results: The study shows that through professional training methods to improve the psychological quality of young boxers, these sportsmen should also recognize the importance of psychological training. Conclusion: Technical help in this approach can complete healthy training, aiming to meet the demands of the sport and collaborate to achieve better results.